The function and significance of neurovascular unit in ischemic stroke therapy - Guoyuan YANG; Xiaosong HE; Yongting WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2011)
DOI：10.3969/j.issn.1672-6731.2011.02.001